From the capital maintenance rule to the solvency test: some thoughts on the new approach to creditor protection in Malawian company law - Kumwenda, Zumbe Andrew (Department of Commercial Law, 2017)
In July, 2013 Malawi enacted a new Companies Act [Act No. 15 of 2013] replacing the old Companies Act 19 of 1984. The Companies Act, 1984 was basically an adoption of the English Companies Act, 1948 and in line with the English law, it regulated distributions through the classical capital maintenance rule. In contrast, the new Companies Act, 2013 which came into force in May, 2016 has jettisoned the capital maintenance rule. As an alternative to that rule, the Act has introduced for the first time in Malawian company law edifice, the concept of the solvency test. Jurisdictions that have adopted the solvency test in their company law essentially have done so on the basis that company law should focus on the core risk at stake – company insolvency, and that it is meaningless to state that creditors look to the company's capital as a trust fund out which their debts would be settled. Despite having the same theoretical basis for adopting the solvency test, the manner in which the solvency test is defined and applied in a particular statute has significant effects on whether in its operation, the test affords adequate protection to the interests of creditors. This research examines the definition and application of the solvency test under the Companies Act, 2013 so as to determine whether in its operation as a financial restriction for distributions and other company transactions, it will afford adequate protection to creditors. It follows the approach used by Professor Kathleen Van der Linde in her analysis of the solvency and liquidity approach in the Companies Act, 2008. Thus, it analyses the Malawian law by focusing on the two separate elements of the test (equity solvency and balance sheet solvency) as well as other aspects of the test which are likely to raise legal interpretation issues. The twin solvency test adopted in different jurisdictions ordinarily varies in its balance sheet solvency element. Some jurisdictions such as South Africa and New Zealand utilise the net assets approach in their balance sheet test. Others such as New York and Delaware still emphasise on the trust fund doctrine and thus utilise stated capital in their balance sheet test. Malawi is a stated capital/surplus jurisdiction. Its new solvency based regime still focuses on the meaningless trust fund doctrine. The new solvency test approach in Malawi is incomplete and inadequate to fully protect creditors against opportunistic shareholder behaviour. A number of recommendations are made for an effective solvency test approach that will afford adequate protection to creditors against opportunistic shareholder behaviour.